Pengaruh Crosslinker Terhadap Pembentukan Poli Asam Humat yang digunakan sebagai Dye pada Sel Surya DSSC - Kenanga Anzulmi; Hardeli Hardeli (Jurnal Periodic Jurusan Kimia UNP, 2020)
Dye Solar Cell (DSSC) is a device capable of converting solar energy into electrical energy. DSSCs are solar cells that use natural dyes to absorb photons from solar energy. The dye used in this study was poly (humic acid) which was obtained from the polymerization of humic acid using TMPGDE as a crosslinker. Polymerization aims to increase the efficiency of the dye in absorbing photons so that the resulting efficiency is better. The ITO glass coated with TiO2 / Cu was made using the sol-gel method. DSSC is assembled to form a sandwich structure and DSSC efficiency is measured using a digital multimeter. UV-Vis analysis of polymerized dyes showed increased adsorption and batochromic shift from 219nm to 269nm - 301nm. The poly (humic acid) formed in the FTIR analysis was characterized by the presence of epoxy groups with peak characteristics of 808 cm-1798 cm-1 and 750 cm-1 and peaks of 1565 cm-1, 1375 cm-1 according to the ester. , carbonyl, and carboxylic acids due to the CH strain. Maximum efficiency of 7.5% at a crosslinker volume of 200 μL.